2018
DOI: 10.1051/metal/2018015
|View full text |Cite
|
Sign up to set email alerts
|

Comparing fast inductive tempering and conventional tempering: Effects on microstructure and mechanical properties

Abstract: Induction heating processes are of rising interest within the heat treating industry. Using inductive tempering, a lot of production time can be saved compared to a conventional tempering treatment. However, it is not completely understood how fast inductive processes influence the quenched and tempered microstructure and the corresponding mechanical properties. The aim of this work is to highlight differences between inductive and conventional tempering processes and to suggest a possible processing route whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…It is anticipated that the higher heating rates would reduce the austenite grain size, but this needs to be verified. The higher heating rates have been shown to reduce the size of the cementite precipitates observed during induction tempering [10]. With the smaller cementite precipitate size, it is anticipated that the cementite would dissolve more readily in the austenite during rapid heating and lead to lower Ms temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…It is anticipated that the higher heating rates would reduce the austenite grain size, but this needs to be verified. The higher heating rates have been shown to reduce the size of the cementite precipitates observed during induction tempering [10]. With the smaller cementite precipitate size, it is anticipated that the cementite would dissolve more readily in the austenite during rapid heating and lead to lower Ms temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated how microstructure and mechanical properties can be significantly modified by induction heat treatments applied to a wide range of iron-based materials and applications. Different research papers investigated the influence of operating parameters on the mechanical properties, with the focus on bulk materials [5][6][7], superficial aspects [8,9] and welded parts [10,11]. Guo et al [12] showed how the combination of the induction heat and surface peening treatments improved the yield strength without significantly impacting the ductility of pure iron.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies demonstrated how microstructure and mechanical properties can be significantly modified by induction heat treatments applied to a wide range of iron-based materials and applications. Different research papers investigated the influence of operating parameters on the mechanical properties, with the focus on bulk materials [5][6][7], superficial aspects [8,9] and welded parts [10,11]. Guo et al [12] showed how the combination of the induction heat and surface peening treatments improved the yield strength without significantly impacting the ductility of pure iron.…”
Section: Introductionmentioning
confidence: 99%